Supply Chain Disruption Management: Severe Events, Recovery, and Performance. Issue 4 (December 2013) - Macdonald, John R.; Corsi, Thomas M.
<x xml:space="preserve">Abstract</x> Given their proclivity to occur despite managers' best efforts, disruptions often result in lost sales, lead to large financial losses, and have a negative impact on shareholder wealth and operating performance. Less attention, however, has been paid to improving the process of managing a disruption from its discovery through to complete recovery. This entire process is not, in fact, fully understood. Clearer insights are needed surrounding the following issues: factors influencing the recovery process, how those factors interact to play a role in managerial decision making, and the company's actual ability to recover. While it is possible to determine basic recovery process factors, a more complete picture of disruption management can be built from analysis of data collected through qualitative in‐depth interviews. This research delivers insights around the interactions and relationships among factors, providing the foundation for a set of propositions useful for further investigation in the following areas: discovery of the disruption event, causes of the event, and recovery performance. One finding indicates that while internal disruptions are faster to recover from, they more likely lead to negative perceptions about the recovery performance outcome.